Clinically actionable pharmacogenomic landscape of antidepressants and antipsychotics in Qatar: a population-based cohort study - Dinesh Velayutham; Kholoud Bastaki; Areeba Irfan; Mohammed Abuhaliqa; Aisha AlMulla; the Qatar Genome Program Research Consortium; Suhaila Ghuloum; Muhammad Waqar Azeem; Munir Pirmohamed; Puthen Veettil Jithesh (Cambridge Prisms: Precision Medicine)
Consortia like the Clinical Pharmacogenetic Implementation Consortium (CPIC) and the Dutch Pharmacogenetic Working Group (DPWG) provide clinical guidelines but pharmacogenomics implementation depends on population prevalence of actionable genetic variants and response phenotypes. We analyzed the distribution of actionable genetic variants and clinical recommendations in 14,354 adult Qataris, focusing only genes with guidelines (CYP2C19, CYP2D6, CYP2B6 and CYP3A4). Haplotypes and diplotypes were generated from 490 alleles using whole genome data and metabolizer phenotypes were predicted based on current knowledge. Qatari population predicted to have actionable metabolizer phenotypes of CYP2C19, CYP2B6 and CYP2D6 impacting response to antidepressants were in the range of 1%–58% and for antipsychotics 0.1%–33% based on CYP3A4 and CYP2D6. Fine-grained analysis based on clinical guidelines also revealed that while the Qataris may need prescription of an alternate antidepressant not metabolized by CYP2C19, patients from other populations may just need altering the dosage of tricyclic antidepressants like amitriptyline. Further studies incorporating other factors such as diet, environment and cultural habits alongwith population-specific variants will help in the pharmacogenomics implementation in the Qatari population.